Polypharmacy and potentially inappropriate medication in elderly of Northern Portugal - Pinto, Isabel C. (2015)
Introduction: The growing aging of population and increasing prevalence of chronic diseases require the simultaneous use of drugs, lead to the issue of polypharmacy and potentially interactions and inappropriate use. Aim: To characterize polymedicated elderly and related factors, identify potentially interactions and inappropriate medication in elderly. Material and Methods: This cross-sectional study was based on a questionnaire applied to 69 elderly (≥65 years) from northern Portugal. It was considered as polymedicated seniors taking ≥5 drugs. Beers list and the Delafuente classification were used to evaluate the therapeutic and possible interactions. It was used descriptive statistics and a model of binary regression, with a significance of 5%. The study was approved by Ethics Committee. Results: The sample consisted mainly of males (53.6% vs. 46.4%), aged between 66 and 99 years (mean 82.01), while 65.2% have more than 80 years. However, most elderly are not polymedicated (58%), on average 4.61 different drugs are administered per day (maximum=19), antihypertensives (36.2%) and antacids (30.04%) are the most prescribed. Hypertension and depression increase the risk of polymedication eightfold (p=0.004) and fivefold (p=0.011) respectively. Female gender seems increase the risk of polypharmacy threefold, although not statistically significant (p=0.102), and regarding age, the older age group (>85 years) seems reduces the risk of polypharmacy in 0.6 fold, but also not statistically significant. According with Delafuente classification, 1.4% of elderly has potentially drug interactions (Omeprazole and Iron salts). According to the list of Beers, 5.8% of seniors take drugs that classified as having some indications (hydroxyzine, amitriptyline). Conclusions: Regarding polypharmacy, 42% of elderly are polymedicated with an average of about 5 different drugs per day, antihypertensives and antacids the most prescribed. Hypertension and depression are highly associated with polypharmacy. We identified one potentially drug interaction and about 6% of elderly taking drugs that classified as having some indications.